Análise das viabilidades da obtenção de um biofilme a partir do colágeno de frango - Gardim, Roberta Bezerra (2018)
The present work aims to analyze the feasibility of obtaining a biofilm from the extraction of collagen from the feet of chicken. In this sense, a factorial design varying the acetic acid concentration, time and temperature of the collagen extraction was used. The optimization of the system was done by response surface analysis with a confidence level of 95% using the ANOVA methodology. After obtaining the collagen, the films were made from a solution of chicken collagen with glycerin or propylene glycol. Biofilms were tested for swelling and water vapor transmission to assure quality and evaluate the prospects for degradation and degree of hydration. It was also evaluated the cost value of raw materials for the production of a pack with 12 units of these biofilms. The dried and pulverized material was found to have a yellow coloration and a composition of more than 78% protein. The extraction yield varied from 1.7 to 8.5% of collagen on the initial mass of the chicken feet and the optimization showed that it is possible to obtain yields above 8.0% when using the acetic acid concentration between 3,000 and 3.682%, the operating time between 1 and 3h and the temperature between 70 and 76.82 ° C. The results of swelling and water vapor transmission tests ensured the quality of products with respect to degradation and degree of hydration. The cost analysis showed that in order to produce a package with 12 biofilm units, the cost of raw material involved was R $ 0.04 (US $ 0.01) and that methylparaben accounted for 75% of the costs, followed by plasticizer (glycerine and / or propylene glycol) with approximately 20% of the total cost of the formulation. Thus, this work demonstrated that biofilms produced from chicken collagen are technically and economically viable.